The Influence of Self-Instruction Techniques on Students’ Self-Efficacy and Career Choices - Ayu Dini Ardianti; Harmanto Harmanto; I Gusti Putu Asto Buditjahjanto; Lilik Anifah (Jurnal Pendidikan : Riset dan Konseptual, 2024)
The high number of vocational school graduates who are employed often find that their competencies and skills do not align with their work. Providing vocational school students with career direction and guidance is crucial so they can focus on developing the necessary skills for suitable job opportunities. This study aims to investigate the impact of self-instruction techniques on students' self-efficacy and career decisions at SMK Negeri 1 Kras, Kediri Regency. The research employed a posttest-only control group design with 71 students divided into two guidance and counseling groups. One group received guidance and counseling using self-instruction techniques, while the other group followed conventional methods. Data collection was done through questionnaires, and hypothesis testing was conducted using MANOVA data analysis. The research findings indicate three key points: 1) Self-instruction significantly affects students' self-efficacy, 2) Self-instruction significantly influences students' career choices, and 3) Self-instruction plays a vital role in students' career decisions. Teaching self-directed techniques concurrently impacts students' self-efficacy and career choices, positively influencing students in making well-informed career decisions.